2021
DOI: 10.1002/cbin.11583
|View full text |Cite
|
Sign up to set email alerts
|

VDAC1 promotes cardiomyocyte autophagy in anoxia/reoxygenation injury via the PINK1/Parkin pathway

Abstract: Ischemia/reperfusion (I/R) is a well‐known injury to the myocardium, but the mechanism involved remains elusive. In addition to the well‐accepted apoptosis theory, autophagy was recently found to be involved in the process, exerting a dual role as protection in ischemia and detriment in reperfusion. Activation of autophagy is mediated by mitochondrial permeability transition pore (MPTP) opening during reperfusion. In our previous study, we showed that MPTP opening is regulated by VDAC1, a channel protein locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…When an acute myocardial injury, such as myocardial infarction, occurs, cardiomyocytes are in a state of stress and their mitochondria are extremely vulnerable to damage ( Ji et al, 2016 ; Alakoski et al, 2019 ; Lassen et al, 2021 ), so autophagy is crucial to eliminate damaged mitochondria and avoid further oxidative stress and apoptosis ( Kubli et al, 2015 ). PINK1/Parkin-induced mitophagy was found to be significantly upregulated during myocardial stress in response to ischemia and hypoxia ( Steffen et al, 2020 ; Yang et al, 2021b ). The loss of PINK1 was reported to inhibit mitophagy and induce reactive oxygen species accumulation and inflammation, leading to cardiomyocyte death and myocardial dysfunction ( Dhanabalan et al, 2020 ).…”
Section: Receptor-dependent and Receptor-independent Pathwaysmentioning
confidence: 99%
“…When an acute myocardial injury, such as myocardial infarction, occurs, cardiomyocytes are in a state of stress and their mitochondria are extremely vulnerable to damage ( Ji et al, 2016 ; Alakoski et al, 2019 ; Lassen et al, 2021 ), so autophagy is crucial to eliminate damaged mitochondria and avoid further oxidative stress and apoptosis ( Kubli et al, 2015 ). PINK1/Parkin-induced mitophagy was found to be significantly upregulated during myocardial stress in response to ischemia and hypoxia ( Steffen et al, 2020 ; Yang et al, 2021b ). The loss of PINK1 was reported to inhibit mitophagy and induce reactive oxygen species accumulation and inflammation, leading to cardiomyocyte death and myocardial dysfunction ( Dhanabalan et al, 2020 ).…”
Section: Receptor-dependent and Receptor-independent Pathwaysmentioning
confidence: 99%
“… 23 VDAC1 regulate PINK1/Parkin pathway to promote autophagy, thereby aggravating anoxia/reoxygenation-induced apoptosis of cardiomyocytes. 24 Qiliqiangxin, a traditional Chinese medicine compound, inhibits apoptosis of cardiomyocytes and improves heart function in myocardial infarction rats by regulating PINK1/Parkin pathway-mediated mitophagy. 25 In the present work, we observed downregulation of PINK1 and Parkin, and increased levels of PINK1 ubiquitination in CIH rats.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have revealed that the regulation of PINK1/Parkin pathway is critical for the alleviation of MIRI. For example, Yang and co-workers have found that the suppression of PINK1/Parkin pathway by VDAC1 downregulation could attenuate MIRI ( 65 ). Additionally, the regulation of PINK1/Parkin pathway by the inhibition of myosin IIA-actin interaction-induced actomyosin contractility could impede MIRI ( 66 ).…”
Section: Discussionmentioning
confidence: 99%